ALTERNATIVE IN VITRO MEDIA FOR MEDIUM-TERM CONSERVATION OF CHRYSANTHEMUM (Dendranthema grandiflora Tvelve) - Budiarto, Kurniawan (Bumi Lestari; Vol 9 No 1 (2009), 2009)
Sufficient genetic diversity and gene pool conservation are needed to serve breeding activities of chrysanthemum. In the tropics, in vitro conservation was expected to be a breakthrough in alleviating the limitation of in vivo methods. A previous study using osmotic pressure methods in low temperature has successfully preserved chrysanthemum via in vitro for medium-term conservation. Modified nutrient compositions were also predicted to have the same impact as far as these concerned. The research was then, conducted to evaluate in vitro conservation of chrysanthemum using media modification in low temperature. The research was carried out on the Indonesian Ornamental Crops Research Institute (IOCRI) from January, 2007 to March, 2008. A randomized completely block design with 25 replications was utilized to accomplish the combination of two factors. The first factor was six commercial chrysanthemum cultivars, namely cv. Puma, cv. Kermit, cv. Town Talk, cv. Snowdown, cv. Yellow Fiji and cv. Saraswati. While the second factor dealt with four formulations of conservation media i.e. ½ MS + DMSO 2,5 % + 4 % sucrose, modified hyponex + 4 % sucrose, modified hyponex (no sucrose) and ½ MS + 4 % sucrose (control). The results showed that the medium term of in vitro conservation for chrysanthemum were successfully conducted up to 12 months using ½ MS + DMSO 2,5 % + 4 % sucrose and modified hyponex + 4 % sucrose without any significant differences and decreases in viability when transferred in to shoot induction media. In the absent of sucrose, however, the planlet survival rates decreased on the media of modified hyponex after 8 months of storage. No significant variation was observed among the chrysanthemum accessions tested.
Keywords: Chrysanthemum (Dendranthema grandiflora), accessions, medium-term conservation, in vitro media, low temperature